2004
DOI: 10.1016/j.joca.2004.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide sustains nuclear factor kappaB activation in cytokine-stimulated chondrocytes

Abstract: The studies indicate that while nitric oxide is not required for immediate NF-kappaB activation in cytokine-stimulated chondrocytes, its effect is to sustain nuclear translocation of p65 and thereby provide a persistent "on signal" to NF-kappaB dependent gene transcription. Persistent activation of NF-kappaB may represent a mechanism by which nitric oxide sustains catabolic processes and promotes cartilage degeneration in osteoarthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 23 publications
5
57
0
Order By: Relevance
“…The activation of p38 MAP kinase and NF-κB nuclear translocation by HA oligos are in common with the stimulation of NO due to treatment of cells with IL-1 (Badger et al, 1998;Clancy et al, 2004;Mendes et al, 2001). In this study we demonstrated that this similarity was not due to HA oligos -induced autocrine release of endogenous IL-1 (Fig.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The activation of p38 MAP kinase and NF-κB nuclear translocation by HA oligos are in common with the stimulation of NO due to treatment of cells with IL-1 (Badger et al, 1998;Clancy et al, 2004;Mendes et al, 2001). In this study we demonstrated that this similarity was not due to HA oligos -induced autocrine release of endogenous IL-1 (Fig.…”
Section: Discussionsupporting
confidence: 73%
“…Using a protein-DNA array screen and EMSA analyses we have also observed the induction of NF-κB in bovine articular chondrocytes treated with HA oligos as well as purified HA 6 (Ohno et al, 2005). Given that increased activity of NF-κB is closely associated with iNOS induction (Clancy, Gomez, & Abramson, 2004) these results suggest a possible mechanism for the increases in the iNOS and NO production following HA oligos stimulation. As well, HA oligos induced iNOS expression in BV-2 microglia mediated by a p38 MAP kinase-dependent pathway (Wang et al, 2004).…”
Section: Discussionmentioning
confidence: 67%
“…The reason for the slightly higher incidence in the AZD3582 375 mg and 750 mg twice a day groups than in the naproxen recipients is not known. Although inducible nitric oxide may alter cartilage metabolism by a number of possible mechanisms (29), the effects of exogenous nitric oxide or nitric oxide in the presence of NSAIDs (30) are not known; no evaluation of cartilage integrity was undertaken in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, however, it is likely that TNF-α as one of catabolic cytokines is produced by cartilage in osteoarthritis that could function as effectors of chondrocyte apoptosis (Fernandes et al, 2002). Production of TNF-α results in high level of nitric oxide (NO), which in turn induces chondrocyte apoptosis (Clancy et al, 2004). Our previous study showed that T-2 toxin increased the production of TNF-α (Li et al, 2008).…”
Section: Rt-pcr Detection Of Bax Bcl-xl Bcl-2 P53 Fas and Caspasementioning
confidence: 99%